Analisis Kreativits Guru Kelas Dalam Menyusun Lembar Kerja Peserta Didik (LKPD) Mata Pelajaran Matematika Masa Pandemi Covid-19 - Nada Wulandari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
The problem in this research is the creativity of the teacher in compiling LKPD. This research is a qualitative descriptive research. Aims to determine the creativity of teachers in compiling LKPD. The results of this study indicate that the teacher's ability to prepare LKPD is good enough in analyzing the material into the LKPD. teacher creativity in LKPD there is a display of images and colors that are in accordance with the material this can increase the attractiveness of students in learning. The conclusion in the creativity of teachers in compiling LKPD at SD Inpres 6/75 Ta is good, but teachers must try to increase creativity in the learning process so that students can be more active in the learning process.